Impact of climate and land use change on the water resources of a large scale catchment in the Cerrado region, Brazil. - WEHLING, M. (2016)
Dissertação (Mestrado em Terra e Meio Ambiente)- Wageningen University, Arnhem, 2016. Lineu Neiva Rodrigues.